Psychiatry and mental health teaching programs of eight portuguese-speaking schools of medicine: A comparative analysis - Pedro, Maria Rosel; Palha, Antonio Pacheco; Ferreira, Maria Amelia (Frontiers in Public Health, 2022)
Background: Improvement of teaching methods in psychiatry has been the subject of permanent adaptation and innovation. strengthening graduate education skills in psychiatry and mental health will allow physicians to have the knowledge, skills and attitudes to carry out early diagnosis and treatment at primary health care settings, taking into consideration that the population should benefit from the best interventions by general practitioners. Objective: Examine how the undergraduate program of psychiatry and mental health subject in the schools of medicine of the Community of Portuguese Speaking Countries in the three continents is structured. Methods: A narrative description of the program of psychiatry, the workload, the delivery and assessment methods and the ethical and socio-cultural aspects in psychiatry and research made by the director of the course of psychiatry in Portugal, Brazil and Mozambique. Results: Eight schools of medicine from Portugal, Brazil and Mozambique participated in the study. all these schools use standards which are defined by the regulatory bodies of their countries. The teaching year varied between the third and the sixth. The workload varied between 140 hours and 224 hours and. Topics were addressed in presence or virtual methods. Combined qualitative and quantitative assessment is done to encompass competencies, skills and knowledge based on clinical histories, ongoing assessment, seminars and final written tests. Ethical and socio-cultural aspects in various strands are taught linked to the local reality. Research is encouraged by using grants. Conclusion: Teaching Psychiatry follows global and national standards and is organized according to the reality of each country. Psychiatry Departments from these three Continents invest in teaching methodologies that encourage self-knowledge and the development of critical thinking, which is evaluated in a holistic context. The authors consider that the programs should have a workload according to the current burden of mental illness.